PEMANFAATAN LIMBAH AMPAS TAHU, PELEPAH PISANG DAN CANGKANG TELUR MENJADI PUPUK ORGANIK PAPICA GUNA MENSEJAHTERAKAN RAKYAT - Fajar Fadhilah Abdul Azys; Kholis Widodo; Bramasta Barella Arsana; Denny Oktavina Radianto (KOLONI, 2023)
Indonesia is a country that has a tropical climate. So that the soil conditions are fertile and many kinds of plants grow. As for some plants whose utilization has not been maximized including banana and soybean fronds. Many people underestimate the banana fronds. In fact, when traced a lot of content that is in it. Meanwhile, if soybeans are used to make tofu, the dregs will just be thrown away. Even though the protein content in it can nourish plants. Not only the diversity of plants, Indonesia is also rich in livestock. Chickens are usually used for meat, feathers and eggs. Most of the use of eggs is for food. However, the use of waste is rarely used, namely egg shells. Egg shells contain good nutrition for plant growth. The tofu dregs of banana fronds and egg shells contain nutrients including calcium, phosphorus, potassium, sodium and amino acids which can help plant growth. On the other hand, the agricultural sector has increased quite rapidly. This causes an increase in fertilizer to help plant growth, one of which is chili. Farmers usually use chemical fertilizers regardless of the negative impact on crop yields or the surrounding environment in the future. Therefore, innovation is needed to utilize tofu waste, banana stems and egg shells to be used as organic fertilizer that is safer to use in the future. above, the authors hope to channel an idea to create alternatives from tofu dregs, banana fronds and egg shells to be used as liquid and solid organic fertilizers to help agriculture and save the environment in the future. Keywords: Banana Stems, Egg Shells, Tofu Dregs.